PENINGKATAN KEMAMPUAN MENYIMAK SISWA DENGAN PENGGUNAAN AUDIO-VISUAL - Farkhatun, Leni; Salim, Herli (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Education is a need where humans as social creatures have the right to obtain education that makes humans more dignified and virtuous. In the process of pursuing education, especially formal education at school, language becomes a medium for transferring knowledge to students both through writing and orally. In conveying thoughts, language skills which include aspects of speaking, listening, writing and reading are mandatory aspects that need to be mastered. In class II of SD Negeri 01 Gendowang, it was found that students' listening learning outcomes were still low. According to the average score resulting from the pre-cycle activities carried out by the researcher, the average score for listening learning was 48.3. This research is aimed at looking at the process of using audio-visuals to improve students' listening skills. Researchers used a qualitative research approach with classroom action research (PTK) methods. The research subjects were class II students at SDN 01 Gendowang, Pemalang Regency. The technique for collecting data was carried out by researchers employing observations carried out in 2 cycles. The results of the two cycles carried out were that students' listening ability increased with the average score for listening learning in cycle I being 72.5 and the average score in listening learning in cycle II being 76.6. This research shows that audio-visual media can improve students' listening skills.